Seventy-two-hour emergency department revisits among adults with chronic diseases: a Saudi Arabian study - Ahmed AE; AlBuraikan DA; Almazroa HR; Alrajhi MN; ALMuqbil BI; Albaijan MA; Alsalamah MA; AL-Jahdali H (Dove Medical Press, 2018)
Anwar E Ahmed,1,2 Doaa A AlBuraikan,2 Hend R Almazroa,2 Manair N Alrajhi,2 Bashayr I ALMuqbil,2 Monirah A Albaijan,1 Majid A Alsalamah,2 Hamdan AL-Jahdali1,2 1King Abdullah International Medical Research Center (KAIMRC), Riyadh, Saudi Arabia; 2King Saud bin Abdulaziz University for Health Sciences, National Guard Health Affairs, Riyadh, Saudi Arabia Background: Despite the increase in adult emergency department (ED) utilization in Saudi Arabia, no studies have evaluated the 72-hour revisits. This study estimates the rate of 72-hour ED revisits and identifies its reasons and predictive factors among adults with chronic diseases. Patients and methods: A hospital-based retrospective study that included 24,206 ED discharges for adults with chronic diseases at the adult ED of King Abdulaziz Medical City, Riyadh between September 13, 2015 and July 29, 2017 was performed. We extracted data on demographic information, reasons for ED visits/revisits, health insurance coverage, weekend ED arrival, and mortality. Results: A sample of 24,206 ED discharges for 19,697 adults with at least one chronic disease was included in the analysis. The rate of 72-hour revisits in this study population was high: 3,144/24,206 (13%) had the first revisit and 319/3,144 (10.1%) had the second ED revisit within 72 hours. Diseases of the circulatory (19%) and genitourinary (15.8%) systems were the major reasons for the first ED revisit. The adjusted relative rate (aRR) of 72-hour ED revisits was higher in adults with chronic diseases and aged ≥60 years (aRR=1.360, 95% CI: 1.41–1.83; P=0.001), patients of female gender (aRR=1.24, 95% CI: 1.09–1.41; P=0.001), patients with health insurance coverage (aRR=4.23, 95% CI: 2.60–6.90; P=0.001), patients arriving to ED on a weekend (aRR=2.13, 95% CI: 1.03–4.41; P=0.041), and new patients (aRR=1.47, 95% CI: 1.25–1.73; P=0.001). Conclusion: The rate of 72-hour revisits is high among adults with chronic diseases. Advancing age, female gender, health insurance coverage, weekend ED arrival, and new patients are the important predictive factors of the high rate of 72-hour revisits. Continuous quality assessment and monitoring of factors related to patients are needed to reduce the frequency of early ED revisits after discharge. Keywords: 72-hour ED revisits, emergency department, KAMC, Saudi Arabia